2022
DOI: 10.1038/s41392-022-01134-4
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based therapy for human diseases

Abstract: Recent advancements in stem cell technology open a new door for patients suffering from diseases and disorders that have yet to be treated. Stem cell-based therapy, including human pluripotent stem cells (hPSCs) and multipotent mesenchymal stem cells (MSCs), has recently emerged as a key player in regenerative medicine. hPSCs are defined as self-renewable cell types conferring the ability to differentiate into various cellular phenotypes of the human body, including three germ layers. MSCs are multipotent prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(237 citation statements)
references
References 501 publications
2
138
0
Order By: Relevance
“…[17] Numerous cell types comprise UCB including HSCs, MSCs, Tregs, monocytes and EPCs. [81] In our review, all four outcomes which demonstrated statistically significant differences between UCB cell types were associated with a favoured modification of treatment effect in MSCs over MNCs. Our review provides further neuropathological support for UCB-MSCs as a potential therapeutic option for infants with perinatal brain injury.…”
Section: Discussionmentioning
confidence: 80%
“…[17] Numerous cell types comprise UCB including HSCs, MSCs, Tregs, monocytes and EPCs. [81] In our review, all four outcomes which demonstrated statistically significant differences between UCB cell types were associated with a favoured modification of treatment effect in MSCs over MNCs. Our review provides further neuropathological support for UCB-MSCs as a potential therapeutic option for infants with perinatal brain injury.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the safety and efficacy of several possible dose levels should be tested in phase I and II clinical trials. Furthermore, the relationship between dose and therapeutic effects needs to be elucidated in pre-clinical settings, by which the minimum effective and saturation levels of the therapeutic agent could be derived [ 56 , 57 ]. In this study, only one dose of ahNSCs was tested for the treatment of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of the cells after drug administration, especially the long-term survival of allogeneic cells during treatment, affects their efficacy. At the same time, there are always some dead cells in cell products, which themselves and their secretions have a worrying impact on the health of patients [ 180 ]. Although many methods have been designed to pretreat MSCs before transplantation to solve these problems, including inflammatory cytokines, hypoxia, drugs, biomaterials and different culture conditions [ 181 ], it is difficult to provide quality assurance for clinical MSC [ 182 ].…”
Section: 'Prohibitor'——evs As a Treatment Of Oamentioning
confidence: 99%